2023
DOI: 10.1001/jamainternmed.2022.7170
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Opt-out vs Opt-in Tobacco Treatment on Engagement, Cessation, and Costs

Abstract: ImportanceTobacco use causes 7 million deaths per year; most national guidelines require people who use tobacco to opt in to care by affirming they are willing to quit. Use of medications and counseling is low even in advanced economy countries.ObjectiveTo evaluate the efficacy of opt-out care vs opt-in care for people who use tobacco.Design, Setting, and ParticipantsIn Changing the Default (CTD), a Bayesian adaptive population-based randomization trial, eligible patients were randomized into study groups, tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…A study in Canada found that with the introduction of the opt-out method, HIV testing rates increased [ 64 ]. Richter et al [ 65 ] revealed the opt-out strategy folded treatment involvement and increased quit efforts. A study exhibited that opt-out protocol resulted in harmless discontinuation of antibiotics in patients with suspected sepsis [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study in Canada found that with the introduction of the opt-out method, HIV testing rates increased [ 64 ]. Richter et al [ 65 ] revealed the opt-out strategy folded treatment involvement and increased quit efforts. A study exhibited that opt-out protocol resulted in harmless discontinuation of antibiotics in patients with suspected sepsis [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other strategies allowing to include smokers unmotivated or ambivalent about cessation include opt-out procedures. Opt-out care can double engagement in tobacco treatment and increase quit rates (Richter et al, 2023). All these strategies could attract smokers not really ready to quit or those never having considered it previously, and allow a preparation period to quitting or a triggering event leading to cessation.…”
Section: Discussionmentioning
confidence: 99%
“…The United States Department of Health and Human Services recently requested information on strategies to broaden the delivery of evidence-based smoking cessation treatments to those who continue to smoke cigarettes (18). Previous studies have demonstrated the effectiveness of an opt-out smoking cessation treatment model for hospitalized patients (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). This study is unique in that it examines practical feasibility of implementing an opt-out smoking cessation treatment model across multiple hospitals serving diverse patient populations.…”
Section: Discussionmentioning
confidence: 99%